2014
DOI: 10.1109/mm.2014.69
|View full text |Cite
|
Sign up to set email alerts
|

Giving Text Analytics a Boost

Abstract: The amount of textual data has reached a new scale and continues to grow at an unprecedented rate. IBM's SystemT software is a powerful text analytics system, which offers a query-based interface to reveal the valuable information that lies within these mounds of data. However, traditional server architectures are not capable of analyzing the so-called "Big Data" in an efficient way, despite the high memory bandwidth that is available. We show that by using a streaming hardware accelerator implemented in recon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Specifically, a FW thread is only responsible for configuring the HW by writing to memory mapped registers, or polling the interrupt status register for data transmission, or receiving incoming data packets. Furthermore, we observe producerconsumer interaction patterns in many practical industrial co-designs from IBM [8,18,19], RockBox Media Player [1], and others codesigns. In this paper, we verify co-designs that exhibit producerconsumer interaction behavior.…”
Section: Proposed Methodologymentioning
confidence: 95%
See 2 more Smart Citations
“…Specifically, a FW thread is only responsible for configuring the HW by writing to memory mapped registers, or polling the interrupt status register for data transmission, or receiving incoming data packets. Furthermore, we observe producerconsumer interaction patterns in many practical industrial co-designs from IBM [8,18,19], RockBox Media Player [1], and others codesigns. In this paper, we verify co-designs that exhibit producerconsumer interaction behavior.…”
Section: Proposed Methodologymentioning
confidence: 95%
“…We have shown that this is extremely beneficial for co-designs that exhibits producer-consumer relationship. Such interaction pattern is prevalent in many practical co-designs [1,8,18,19]. However, the proposed verification approach is not applicable for co-designs that exhibits true concurrency [5], that is, when a SW and its interacting HW threads do not exhibit producer-consumer relationship.…”
Section: Limitations Of Proposed Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…We report an industrial application of HW-CBMC on the Text Analytics FPGA Accelerator (TAA) co-design [14,13]. Text analytics is key in big data analytics.…”
Section: Introductionmentioning
confidence: 99%
“…These raw data typically consist of irregular data types, and are poorly suited for traditional processor register types. In contrast to the initial stages or leaf processing steps, once the data has been filtered and formed into structured data, parallelism is greatly reduced [7].…”
Section: Introductionmentioning
confidence: 99%